Information and its users: a review with special reference to the social sciences - Brittain, J. Michael (Bath, Bath University Press, 1970)
This book stands on its own right, but also represents a giant offshoot of the investigation into information requirements of the social sciences.
Includes bibliographical references, Index
aia 21/6/17
Loans
Keywords: Communication in the social sciences; Information storage and retrieval systems